Is professional commitment the reason for turnover intentions of IT professionals? / Mohamed Buhari Mufitha, Lee Su Teng and Yong Chen Chen - Mufitha, Mohamed Buhari; Lee, Su Teng; Chen Chen, Yong (Universiti Teknologi MARA, Shah Alam, 2019)
Compared to others, professionals share distinguish workplace characteristics: one such is the high commitment to the professions over to working organizations. Information Technology (IT) professionals demonstrate higher turnover rates compared to others: their commitments to the profession has been suspected as a source of turnover. Considering their job satisfactions the present study aimed to investigate the influence of professional commitment on IT professionals’ turnover intentions. Data were collected from a sample of software engineers from Sri Lank using a survey questionnaire. The results of the structural equation model analysis concluded that professional commitment weakens IT professionals’ turnover intentions, which is partially mediated by job satisfaction. Professional commitment stimulates IT professionals’ job satisfaction. The findings challenge the presumption that IT professionals leave their organizations due to high commitments to the profession. Few factors were identified as significant in their job satisfactions: supervision, co-workers and work design. Pay and promotions were the least influencing job satisfaction factors. Managers may employ few strategies in their retention strategies: facilitate professional advancement needs within organizations, closely monitor supervision activities occurs and provide challenging and meaningful jobs. The study contributes to the turnover literature through empirical evidence on the influence of professional commitment on knowledge workers’ turnover intentions.